استخدام منهجية بوكس- جينكنز لبناء نموذج قياسي للتنبؤ بعدد المواطنين السوريين - أحمد طالب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة لتوضيح خطوات استخدام منهجية بوكس – جينكنز في التنبؤ بالسلاسل الزمنية, حيث تقوم هذه المنهجية على الدمج بين نماذج الانحدار الذاتي AR والمتوسطات المتحركة MA, وهدفت أيضاً لوضع نموذج قياسي للتنبؤ بعدد المواطنين السوريين باستخدام هذه المنهجية،وتوفيق أفضل نموذج من نماذج ARIMA. وكانت أهم نتائج الدراسة أنه: تم التوصل إلى نموذج قياسي هوARIMA(2,1,1)، حيث يمكن استخدامه في التنبؤ بعدد المواطنين السوريين حتى عام 2035, وهو أفضل النماذج المقترحة للحصول على تنبؤات دقيقة وفقاً للاختبارات الإحصائية واختبارات الدقة التنبؤية.وتبين من خلال هذا النموذج أنعدد المواطنين السوريين المقدر سيزداد حتى عام 2035. The aim of study was to illustrate the steps of using BOX-JENKINS methodology to predict the time series. This methodology combines between Autoregressive models and Moving Averages. It also aims to develop a standard model for forecasting of Syrian population using this methodology, and estimate the best model of ARIMA models. The main results of the study: It was build ARIMA (2,1,1) model, which can be used to predict of Syrian population until 2035, it was the best model to get on accurate predictions according to statistical tests and predictive accuracy tests. Through of this model, the estimated Syrian population will increase until 2035.